Witnessing the perpetrator: testimony and accountability in current Israeli documentary film. Issue 2 (3rd March 2020) - Duvdevani, Shmulik; Yosef, Raz
ABSTRACT: The article critically examines the ethical stance taken by two Israeli documentary films dealing with perpetrator-victim positions: Ari Folman's Waltz with Bashir (2008) and Avi Mograbi's Z32 (2008). These films, we argue, are seeking for new aesthetic strategies of representing past traumatic events as well as critically and innovatively exploring the ethical position of the perpetrator. At the same time, these films challenge the traditional distinctions between documentary and fiction, reference and representation. The films seek, both aesthetically and ethically, to raise questions regarding the representation of the perpetrator during the First Lebanon War and the Second Intifada without offering a redemptive narrative for Israelis. Through their use of testifiers and testimonies these documentary films challenge the traditional opposed positions of victim/perpetrator.